10‐year experience with lamellar keratoplasty for the surgical Management of Paediatric Corneal Diseases. Issue 6 (9th June 2022) - Pellegrini, Marco; Salgari, Niccolò; D'Angelo, Sergio; Caruso, Lorenzo; Franco, Elena; Bovone, Cristina; Spena, Rossella; Zauli, Giorgio; Busin, Massimo; Yu, Angeli Christy
Abstract: Purpose: To evaluate the outcomes of various lamellar keratoplasty techniques performed at our Institution in children aged 14 years or younger over the last decade. Methods: This single‐centre study reviewed 72 eyes that underwent lamellar keratoplasty for various indications. Deep anterior lamellar keratoplasty (DALK) was performed in 19 eyes, mushroom penetrating keratoplasty (PK) in 27 eyes and Descemet stripping automated endothelial keratoplasty (DSAEK) in 25 eyes. The main outcome measures included best spectacle‐corrected visual acuity (BSCVA), complications and rate of graft failure which was defined as any graft requiring repeat transplantation. Results: Best spectacle‐corrected visual acuity (BSCVA) significantly improved after DALK, mushroom PK and DSAEK (all p < 0.05), with 50%, 60% and 56% of eyes reaching ≥20/40, respectively. Stromal rejection was observed in 1 eye (5.3%) after DALK, whilst endothelial rejection occurred in 1 eye after mushroom PK (3.7%) and 1 eye after DSAEK (4.0%). Overall survival was 100% after DALK (mean follow‐up: 23.0 months), 92.8% after mushroom PK (mean follow‐up: 42.3 months) and 96.0% after DSAEK (mean follow‐up: 33.6 months). Conclusion: Deep anterior lamellar keratoplasty (DALK), mushroom PK and DSAEK offer good visual outcomes for children with corneal pathology, with low rates of immunological rejection and graft failure.